Mental Health Disorders in Circumcised Reproductive-age Women, Legal Dimensions and Prevention Strategies: A Narrative Review - Alidost, Farzane; Abbasi, Mahmoud; Ghamsari, Sepideh Rezaei; Pakzad, Mona (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective: Female genital mutilation/cutting (FGM/C) can affect women's lives through various physical, psychological, social and even sexual mechanisms. According to the World Health Organization guidelines for managing the health effects of FGM/C, further research into its psychological effects and preventative measures is required. In this study, a comprehensive review of the mental health consequences of circumcised women of reproductive age has been conducted with a special focus on providing preventive solutions.Methods: A comprehensive search of the Web of Science, PubMed(MEDLINE), Proquest, Scopus and Google scholar was carried outfrom 2000 to 2022. The second stage of search was conducted in grey literature. To facilitate a systematic approach to search the literature, the PECO framework, was adopted.Results: The result of this narrative review study showed that, the most common mental health disorder in reproductive age circumcised women were depression, anxiety and post-traumatic stress disorder. Some studies found a significant relationship between parents' education level and circumcised girls, so that parents of the circumcised women had a low level of education. Two studies considered religious beliefs, tradition, cleanness, sexual desire control and virginity as the reasons for FGM/C.Conclusion: All forms of FGM/C may be harmful to one's health. Women, who have undergone widespread forms of circumcision, are more likely to develop mental disorders. As the psychosocial effects of circumcision can affect the sexual experience of circumcised women, addressing this issue, emphasizing its legal aspects, and providing preventative solutions can improve physical, mental, social, and even sexual health in circumcised women.
Keywords: Circumcisions; Female; Infibulation; Clitoridectomy; Genital mutilation; Mental health; Depression